Modeling of the Denitrification/Anaerobic Digestion Process of Salmon Fishery Wastewater in a Biofilm Tubular Reactor - Huilinir-Curio, C (2011)
The literature has paid scarce attention to the modeling of the denitrification-anaerobic digestion process in packed bed biofilm tubular reactors used to treat wastewater. The present study obtained a steady-state model for industrial salmon fishery wastewater treatment in a biofilm tubular reactor, including pH as a variable and the effect of biomass on hydrolysis. The axial profile of the reactor components and process efficiency were predicted with deviations below 6%. The optimal operating zone for the process was found at hydraulic retention time (HRT)>1.5d and inlet protein concentration (Sprot,0)<3000mgTOCL-1. Based on our results, we concluded that the removal of organic matter and nitrogen compounds depended mainly on HRT. The effluent pH was mainly affected by the C/N ratio, where a decrease increases pH. Organic matter removal was related with the anaerobic digestion process, while denitrification influenced mostly nitrate and nitrite removal. © 2011 Elsevier Ltd.